Holland Family : The Jealous Kind - Book 11 - Burke, James Lee 1936-; Patton, Will; Simon & Schuster Audio (Firm) (New York, NY : Simon & Schuster Audio, 2016)
On its surface, life in Houston in the 1950s is as you'd expect: stoic fathers, restless teens, drive-in movies, and souped-up Cadillacs. But underneath lies a world shifting under high school junior Aaron Broussard's feet. There's a class war between the "haves" and the "have-nots" as well as a real war, Korea, happening on the other side of the world. It's against this backdrop that Aaron comes of age, trying to understand how first loves, friendship, violence, and power can alter what "traditional America" means for the people trying to find their way in a changing world.
Keywords: High school juniors -- Fiction; Social classes -- Fiction; Nineteen fifties -- Fiction; Korean War, 1950-1953 -- Fiction; Audiobooks; Houston (Tex.) -- Fiction -- Social life and customs -- 20th century; Bildungsromans; Historical fiction; Audiobooks